The Leadership Role of the Executive Chef in Improving Kitchen Employee Performance at Swiss-Belhotel Ambon - Nur Fajrin; Prima Setia Judha Pranatha (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
The lack of performance of kitchen employees at the Swiss-Belhotel Ambon Hotel is due to the lack of good cooperation, non-compliance with SOPs and also standard recipes that have been made, therefore the leadership role of the Executive Chef is needed to improve the performance of kitchen employees. The purpose of this study is to describe the role of the Executive Chef and to find out how the Executive Chef's leadership efforts improve the performance of kitchen employees at the Swiss-Belhotel Ambon Hotel. The data collection method used is a qualitative method using observation, interview, and documentation data collection techniques. The results of the research are first, the Executive Chef has carried out his role well, namely: as a planner, as a policy maker, as an executor, as an expert, and as a controller in carrying out its role as a leader in the food product department. Second, efforts to improve employee performance, namely: providing training, providing motivation, establishing friendship and providing career paths in order to improve the performance of kitchen employees.